KAJIAN LAJU ANGKUTAN SEDIMEN TOTAL PADA KANTONG LUMPUR BENDUNG AIR MUSI KEJALO - Rahayu, Anis Septia; Besperi, Besperi; Razali, Makmun Reza (Inersia: Jurnal Teknik Sipil, 2018)
Bendung Air MusiKejalo has decreased productivity,one of the contributing factors is sedimentation. The purpose of research is to know the massive rate of sediment transport from weir which enter in sand trap using method of Shen and Hungs and Meyer Petter Muller method. Then plot the dimensions of the sludge pouch from the resulting sediment rate.The stages of the research implementation are sediment sample test, flow velocity measurement and channel dimension then calculation and data analysis.The result of calculation using method of Shen and Hungs, got the value of sediment rate discharge at sand trap is 0,1295 ton / day, and by Meyer Petter Muller method equal to 22,4966 ton / day. So the result of sediment rate discharge Meyer Petter Muller method used for planning dimension sand trap of Air Musi Kejalo Weir.Volume of sand trap Air Musi Kejalo Weir is 120 m3. Dimensions of sand trap length 61 m, width 4 m and depth of 1,3 m. The conclusion of this study is that with thedimensions of planned sludge pockets based on the volume of sediment obtained, the sand trap should be rinsed for 14 days once so that the sediment does not accumulate in the sand trap and using a construction is pairs of round stone with type of sand trap is square and type of main drain is trapezoid.